Sequentially updating the likelihood of success of a Phase 3 pivotal time-to-event trial based on interim analyses or external information. Issue 2 (3rd March 2016) - Rufibach, Kaspar; Jordan, Paul; Abt, Markus
ABSTRACT: When performing a pivotal clinical trial, it may be of interest to assess the probability of success (PoS) of that trial. Initially evaluated when the trial is designed, PoS can be updated as the trial progresses and new information about the drug effect becomes available. Such information can be external to the trial, such as results from trials conducted in parallel, or internal, such as continuing after an interim analysis. We develop a framework to update PoS based on such internal and external information for a time-to-event endpoint and illustrate it using a realistic development program for a new molecule.